Can the combination of antiplatelet or alteplase thrombolytic therapy with argatroban benefit patients suffering from acute stroke? a systematic review, meta-analysis, and meta-regression. - Haiyan Xie; Ying Chen; Wukun Ge; Xiuping Xu; Chengjiang Liu; Zhiyong Lan; Yina Yang (PLoS ONE)
Background The effectiveness of administering argatroban as a treatment approach following antiplatelet therapy or alteplase thrombolytic therapy in patients with acute stroke is presently uncertain. However, it is important to highlight the potential benefits of combining this medication with known thrombolytics or antiplatelet therapy. One notable advantage of argatroban is its short half-life, which helps minimize excessive anticoagulation and risk of bleeding complications in inadvertent cases of hemorrhagic stroke. By conducting a meticulous review and meta-analysis, we aim to further explore the common use of argatroban and examine the plausible advantages of combining this medication with established thrombolytic and antiplatelet therapies. Method In this study, we performed a rigorous and methodical search for both randomized controlled trials and retrospective analyses. Our main objective was to analyze the impact of argatroban on the occurrence of hemorrhagic events and the mRS scores of 0-2. We utilized a meta-analysis to assess the relative risk (RR) associated with using argatroban versus not using it. Results In this study, we analyzed data from 11 different studies, encompassing a total of 8,635 patients. Out of these patients, 3999(46.3%) received argatroban treatment while the remaining 4636(53.7%)did not. The primary outcome of 90-day functional independence (modified Rankin scale (mRS) score≤2) showed that the risk ratio (RR) for patients using argatroban after alteplase thrombolytic therapy compared to those not using argatroban was(RR, 1.00 ([95% CI, 0.92-1.09]; P = 0.97), indicating no statistical significance. However, for patients using argatroban after antiplatelet therapy, was (RR,1.09 [95% CI, 1.04-1.14]; P = 0.0001), which was statistically significant. In terms of hemorrhagic events, the RR for patients using argatroban compared to those not using argatroban was (RR,1.08 [95% CI, 0.88-1.33]; P = 0.46), indicating no statistical significance. Conclusion The results of this study suggest that further research into combination therapy with argatroban and antiplatelet agents may be warranted, however more rigorous RCTs are needed to definitively evaluate the effects of combination treatment.